2012
DOI: 10.1590/s0100-69162012000600004
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal thermal comfort in facilities for growing swines

Abstract: ABSTRACT:In most of Brazilian pig farms, the environmental acclimatization systems run manually. For night and early morning periods, this practice isn't appropriate, because, in general, there are not employees available to run these manual systems. This research aimed to compare the bioclimatic profile of two differently constructed facilities to the external environment, considering the period from 6 p.m. to 6 a.m. during the spring, in order to show that night and early morning temperatures do not coincide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…The THI with the fiber-cement tiles was higher (1.0) than that of the clay tile. The result is in agreement with SARUBBI et al (2012), who found an increase on THI of 3.0 in pigs reared under building using the roof of fiber-cement tiles, compared to clay tile during spring. In the present study, the variation of the Ta from clay tile was 3.0 °C and RH 9.5%.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The THI with the fiber-cement tiles was higher (1.0) than that of the clay tile. The result is in agreement with SARUBBI et al (2012), who found an increase on THI of 3.0 in pigs reared under building using the roof of fiber-cement tiles, compared to clay tile during spring. In the present study, the variation of the Ta from clay tile was 3.0 °C and RH 9.5%.…”
Section: Resultssupporting
confidence: 92%
“…Following the recommendation in this past study by BARBARI & CONTI (2009), sows and piglets are thermally uncomfortable in both rooms (clay and fiber-cement tiles), and this condition is critical to pig production. THI values for pigs were estimated during spring in an environment with clay (73 ± 4.0) and fiber-cement tiles (76 ± 4.0) (SARUBBI et al, 2012). In the present research, just pigs reared in pens with clay tile were in thermal comfort.…”
Section: Resultsmentioning
confidence: 58%
“…For structural issues it was observed that the leaked floor has an advantage over the massive one of 1.70%, and the roof with cement tile type took advantage of 3.60% over the clay tile although most of the nationwide, almost entirely, the clay tile has advantages to fiber cement ("asbestos") due to the physical characteristics of the products (thermal conductivity, thermal delay and damping) (ABCS, 2011;SARUBBI, 2012).The isolation was a favorable trend for producers using bio-security facilities accessed by a building containing office, dressing room, and pharmacy, in attention to the rules that prevent access and movement of people and vehicles to the farm according to the recommended by EMBRAPA (2003).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that ambience presents little contribution to total sample variation by PCA, it directly influences the animal thermal comfort, especially in Mato Grosso do Sul State, which is located in the Cerrado where climate is predominantly hot and dry. Swine welfare is influenced by climatic conditions that, at certain times of the year, exceed the limits of animal comfort (SARUBBI et al, 2012).…”
Section: Resultsmentioning
confidence: 99%